Functional Relevance of Missense Mutations Affecting the N-Terminal Part of Shank3 Found in Autistic Patients - Hassani Nia, Fatemeh; Kreienkamp, Hans-Jürgen (Frontiers in Molecular Neuroscience, 2018)
Genetic defects in SHANK genes are associated with autism. Deletions and truncating mutations suggest haploinsuffiency for Shank3 as a major cause of disease which may be analyzed in appropriate Shank deficient mouse models. Here we will focus on the functional analysis of missense mutations found in SHANK genes. The relevance of most of these mutations for Shank function, and their role in autism pathogenesis is unclear. This is partly due to the fact that mutations spare the most well studied functional domains of Shank3, such as the PDZ and SAM domains, or the short proline-rich motifs which are required for interactions with postsynaptic partners Homer, Cortactin, dynamin, IRSp53 and Abi-1. One set of mutations affects the N-terminal part, including the highly conserved SPN domain and ankyrin repeats. Functional analysis from several groups has indicated that these mutations (e.g. R12C; L68P; R300C and Q321R) interfere with the critical role of Shank3 for synapse formation. More recently the structural analysis of the SPN-ARR module has begun to shed light on the molecular consequences of mutations in the SPN of Shank3. The SPN was identified as a Ras association domain, with high affinities for GTP-bound, active forms of Ras and Rap. The two autism related mutations in this part of the protein, R12C and L68P, both abolish Ras binding. Further work is directed at identifying the consequences of Ras binding to Shank proteins at postsynaptic sites.